Semi-active inerters: a review of the literature - Tran, Kim Thach; Jin, Shida; Deng, Lei; Du, Haiping; Nguyen, Hung Quoc; Li, Weihua (Frontiers in Materials, 2024)
The inerter was introduced as a mechanical counterpart to the electrical capacitor, completing the forcecurrent analogy. This is a one-port, two-terminal device in which the equal and opposite forces exerted at its terminals are proportional to the relative acceleration between them. Within this relationship, the "inertance" is the coefficient of proportionality and carries the unit of mass. This implies that the inerter can exert an inertial force at its terminals, effectively representing a virtual mass. Due to these properties, inerters have gained popularity, finding applications as components of vibration control systems and energy harvesters. Derived from passive inerters, semi-active inerters are integrated with active control systems to regulate their inertance. Since their introduction, semi-active inerters have been pivotal in situations demanding active monitoring of natural frequency or control force, generally outperforming their passive counterparts. While numerous significant reviews on passive inerters and their applications have been published in respected journals, dedicated literature reviews on semiactive inerters remain scarce. This review seeks to bridge this gap, offering a comprehensive literature review on semi-active inerters and highlighting research challenges and opportunities. Given the novelty of semi-active inerters, they present a fascinating area of study.This article was written in British English as the authors are affiliated to an Australian institute. All figures and tables are included in the 'Supplementary Material' document submitted along with the main document.